Efeito de diferentes estratégias de irrigação sob as culturas de feijão (Phaseolus vulgaris L.) e milho (Zea mays L.) na região de Santiago, RS - Parizi, Ana Rita Costenaro (2007)
Water is one of the production factors that limit the most the output of cultivated plants. In regions in which the rain distribution is irregular, it may occur significant losses in the output of cultures. In these cases, the supplemental irrigation is a technology that can be used to reduce the risks of low production, not to mention to propitiate a greater number of crops during the year. This dissertation was developed on the experimental area of Fazenda Liberdade, situated in the municipal district of Santiago, RS. The aim of this work was to evaluate the behavior of the beans and corn cultures in order to obtain growth, development and production parameters under different irrigation strategies, and to verify which strategy results in the highest productivity for the region of Santiago, RS. Bean cultivars FT Nobre and corn AGN 2012 were used. The irrigation manipulation was based on a prefixed shift of irrigation, with an interval of 5 days. The irrigation blades applied along the vital cycle of the cultures were done based on the database of evapotranspiration measured in evapometric Mini-Tank, that being 60%, 80%, 100%, and 120% of the value of evotranspiration (ETo) as reference. In a fifteen days period the growth and development parameters were measures, such as the leaf area index (LAI) and the plants height; in a period of ten days the covered surface for the beans was measured. The productivity components were determined for both cultures in the crop. It was also verified the efficiency in water use (EWU). The results were submitted to variance analysis and to the F test at 5% probability level. The averages were compared among each other by the Tuckey Test at 5% probability level. The results obtained show that no statistically significant differences occurred in the growth and development parameters for both cultures. There were statistically significant differences for most productivity components of beans; these differences were less evident with corn. The cultures submitted to the irrigation strategy of 80% of ETo show greater expansion. The LAI determination for beans may be done through covered surface measurements from time to time. The greatest grain production for beans was obtained with the irrigation strategy of 80%, and for corn it occured with the irrigation strategy of 100%, followed by greater values of EWU. The implementation of supplemental irrigation elevates the productivity of the cultures studied in the West-frontier region of Rio Grande do Sul for the conditions, considered characteristics of the period and factors.